Islamic Court’s Approach to Land Dispute in Inheritance Cases - Lego Karjoko; Abdul Kadir Jaelani; Hilaire Tegnan; Henning Glaser; Muhammad Jihadul Hayat (AHKAM : Jurnal Ilmu Syariah, 2021)
This study examines the legal considerations in settling inheritance disputes involving land distribution in Selong Religious (Islamic) Court of West Nusa Tenggara. The data in this study were obtained from interviews and court decision analysis. This study shows that the practice of granting property before the death of the muwārith (testator) can cause inheritance-based land disputes in the future. Disputes usually arose when the land was distributed only to particular heirs, neglecting the others, especially the daughters and their descendants. In deciding the land disputes in inheritance cases, judges evermore considered the legal validity of the land distribution. Besides that, the judges use Islamic legal sources such as the Quran, Hadith, opinions of scholars, and fiqh in their legal considerations. However, the use of these multiple references does not necessarily lead to a diverse outcomes.  Abstrak: Penelitian ini mengkaji bagaimana pertimbangan hukum hakim dalam memutus perkara sengketa hibah tanah di Pengadilan Agama Selong, Nusa Tenggara Barat. Data pada penelitian ini diperoleh dari wawancara dan analisis putusan. Penelitian ini menunjukkan bahwa kebiasaan masyarakat menghibahkan harta sebelum kematian pewaris cenderung menjadi pemicu sengketa tanah berbasis waris di kemudian hari. Sengketa biasanya muncul dari pembagian tanah yang hanya kepada sebagian ahli waris dan merugikan sebagian ahli waris yang lain, terutama bagi anak perempuan dan keturunannya. Dalam memutus sengketa hibah tanah dalam kewarisan, hakim selalu mempertimbangkan keabsahan hukum hibah tanah dalam kasus yang diajukan. Selain itu, hakim juga menggunakan ayat-ayat al-Qur’an, hadis, pendapat ulama, dan kaidah fikih sebagai pertimbangan hukumnya.